Rancang Bangun Prototype Sistem Pengendali Suhu dan Kelembaban pada Penyimpan Tepung - Annisau Saidah (Politeknik Negeri Malang, 2017)
Storage of wheat flour requires good temperature and humidity to avoid mold growth that can damage the nutrients in wheat flour. The temperatures and humidity required for proper storage are above temperatures and humidity below 60% RH. The method used in flour storage is FIFO (First In First Out) using a Load cell sensor as a marker for flour input. The incoming flour will input the time, location and amount of flour, so that it can be easily determined which flour will come out first. To facilitate monitoring of temperature, humidity and stock amount in flour storage in this study, sending monitoring data wirelessly using an internet network that can be accessed anywhere. The test results of this study show that the DHT22 sensor can measure temperature and humidity well, which has a RE (Relative Error) value of 0.5% temperature and 3.9% humidity compared to the HTC-1 measuring instrument. The load cell test compared to digital scales has an accurate value using a linear formula. In the QoS test, sending sensor data to the web server has a good value according to the ITU-T standard, namely delay <150ms